The Interaction of Legal Awareness and Legal Culture on the Dynamics of Social Order among Generation Z - William Wun; Siska Aprelyani (Greenation International Journal of Law and Social Sciences, 2024)
Literature Review on the interaction between legal awareness and legal culture as determinants of social order among Generation Z is a scientific article with the objective of analyzing whether legal awareness and legal culture play a role in shaping the dynamics of social order among Generation Z in the digital era. This research method using document analysis by reviewing relevant national and international journal articles, academic books, and scientific publications related to Generation Z, legal awareness, legal culture, and social order. The results of this article indicate that: 1) legal awareness significantly influences the formation of social order among Generation Z, particularly through reflective and evaluative legal compliance; 2) legal culture plays a crucial role in shaping legal legitimacy, trust, and patterns of compliance, especially within digital and participatory social environments. The interaction between legal awareness and legal culture determines the stability and sustainability of social order in contemporary society. In addition to these two exogenous variables, social order is also influenced by other factors, including legal legitimacy, digital norms, social values, and the effectiveness of legal education and public participation